A decade of monitoring the Critically Endangered Madagascar Pochard Aythya innotata: population trends and duckling survival - Rasoamihaingo, Laurence A.; Razafindrajao, Felix; René de Roland, Lily-Arison; Bamford, Andrew J. (Wildfowl, 2024)
Factors affecting the breeding success of tropical ducks is an under-researched and poorly understood topic. Here we look at the Critically Endangered Madagascar Pochard Aythya innotata, rediscovered in 2006 at a single location, Bemanevika, in northern Madagascar. Local abundance and duckling survival at the site has been monitored since 2010, during which time numbers increased from 20 to 60 individuals. Timing of breeding was variable between years, but in general most broods hatched in the late dry season (September–November). Duckling survival was low (4%, range = 0.1–18% over the years); however, there were three years of unusually high duckling survival (2017–2019), which seem to have been the driver of the population increase. In contrast to most studies of ducklings, we found higher mortality rates as duckling age increased, peaking at 14 days old. We review the available evidence, for and against five main hypotheses, to explain the low breeding success recorded in this population: predation, food availability, disease, weather and timing of breeding. Predation and timing are not strongly supported as causes of low breeding success. Food availability and weather have evidence in their favour but based, on the evidence currently available, are not able to explain the observed population increase conclusively, suggesting no single overarching cause of the problem. Instead, several of the hypotheses may interact. Future monitoring should focus on collection of more data on disease and food availability.